Letter (copy) - Tewson, Vincent
025a-0009-001 International. HVT/AC/DT/414. 2nd January, 1941. Mr. J.M. Luzmore, Immigration Branch, Home Office, P.O. Box No. 2. BOURNEMOUTH. Dear Sir, Adverting to your letter of the 7th of December, I have now received information with regard to the whereabouts of two of the persons named. We have been informed that Jose Larrabeiti is at the present time sailing in a Spanish ship between Spain and South America. The last time he was heard of in England, we learn, was when he Joined a Spanish boat at Cardiff. Our informant is ignorant of the date of his departure, however, and enquiries made at the Sailors' Home, Dock Street, London, E.1 (to which we were referred for possible additional information) have proved fruitless. it is confirmed that Sebastian Prat is sailing between the Americas in the Panama ship "Cygnet" as wireless operator. As far as we know, his wife is at Nottingham, but our information in this respect is a twelvemonth old. I regret we have now particulars about the other names in your list, and as the remaining man in London, M. Arenaza, who was making enquiries in this matter and supplied the above information has now joined a ship bound for Argentina, I fear it is unlikely that we shall be able to add to it. Yours faithfully, Assistant Secretary. 292/946/25a/9